Moderating effect of self-esteem and depression on the correlation between the frequency of community volunteer activities and job consciousness in dental hygiene students - Jonghwa, Jang (Han'guk Ch'iwisaeng Hakhoe chi, 2018)
Objectives: This study examined dental hygiene students' frequency of participation in community volunteer activities, job consciousness, depression, and self-esteem, and then identified the correlation among them. We also analyzed the moderating effect of depression and self-esteem on the correlation between participation in community volunteer activities and job consciousness. Methods: We surveyed 312 dental hygiene students attending four universities in South Chungcheong Province, Korea, from May 2 to June 15, 2016, through direct visits. They were given structured questionnaires containing four items on community volunteer activities, three on job consciousness, ten on self-esteem, and 13 on depression. To examine the moderating effect of depression and self-esteem, we performed analysis of variance, correlation analysis, and structural equation modeling analysis (based on the path analysis model and by inserting interaction terms) using SPSS and AMOS. Results: We observed a negative correlation between self-esteem and depression (r=-0.062) but a positive correlation between self-esteem and job consciousness (r=0.125). Depression and job consciousness had a negative correlation (r=-0.176). Depression had a statistically significant impact on job consciousness (r=-0.519, p<0.01). The interaction term between depression and frequency of community volunteer activities also had a statistically significant influence on job consciousness (r=0.090, p<0.05). These findings indicate that depression moderates the correlation between frequency of community volunteer activities and job consciousness at a statistically significant level. Conclusions: More frequent participation in volunteer activities enhances dental hygiene students' self-esteem, reduces depression, and raises job consciousness. The positive impact of volunteering on self-esteem, depression, and job consciousness warrants encouraging students' participation in community volunteer activities, creating supportive structures, and developingvarious volunteer programs relevant to the students' area of study. KCI Citation Count: 0